Age effects on transfer index performance and executive control in baboons (Papio papio) - Bonté, Elodie; Kemp, Caralyn; Fagot, Joël (Frontiers in Psychology, 2014)
Reversal performance in the transfer index (TI) task is known to improve from prosimians to apes, suggesting that this task is a marker of cognitive evolution within the primate taxa (Rumbaugh, 1970). However, the cognitive processes recruited by this task remain unclear. In the present study, 19 socially-housed baboons (Papio papio) from 1.6 to 14.3 years were tested on a computerized version of the TI task, using an automated self-testing procedure. Age was a significant factor in the level of success, with the younger baboons outperforming the adults. The younger baboons also learned the pre-reversal discrimination faster and improved their post-reversal performance more rapidly than adult baboons. As the same baboons had been tested in previous studies on inhibitory control and cognitive flexibility tasks, comparison across tasks provide indicators of the underlying cognitive processes. Age variations in performance were similar between the TI task and in an adaptation of the Wisconsin Card Sorting Task measuring cognitive flexibility (Bonté, Flemming and Fagot, 2011). This contrasts previous results from a task requiring motor inhibitory control (Fagot, Bonté and Hopkins, 2013). Therefore, these findings suggest that cognitive flexibility was a central component of the cognitive system that evolved within nonhuman primates. They also implicate a decline in executive control with age that begins during early adulthood in the baboon species.